Penetrasi Budaya Korea Selatan terhadap Nilai-Nilai Pancasila: Analisis dari Perspektif Media Sosial di Indonesia - Geprita Gulo; Anisa Asari Dewi; Elvi Maulida Harahap; Fina Febrian; Nurfadhilah Pasaribu; Wildani Putri Sagala; Winda Afdila Sari; Zahwa Maulidina Assyifa; Fazli Rachman (Jurnal Manajemen Kreatif dan Inovasi, 2024)
Korean culture, especially South Korea, is currently developing very rapidly and widely, resulting in a new phenomenon among teenagers. The much-loved culture is K-Pop, Korean drama(drakor), music, food, and lifestyle. South Korean culture is feared to be the cause of the fading spirit of nationalism among teenagers. The fading of nationalism is a deviation from the values of Pancasila in the third principle which reads "Indonesian Unity". The purpose of writing this scientific article is to find out the breakthrough of South Korean culture on Pancasila values. The approach used in writing this scientific article is a qualitative approach. The method used in writing this scientific article is systematic literature review. This method is expected to be able to provide a broad but still in-depth picture related to the issues or topics raised in the writing of scientific articles. There are 9 journal articles that will be analyzed by the writing team in this article. The authors selected articles from accredited journals and obtained from several electronic search sites, namely Google Scholar, Sinta, and Garuda.